Design, Analysis and Manufacturing Polymer Fiber Reinforced Composite Helical Spring - Hamed, Hadeer Abdul Rasol; Ismail, Mahmud Rasheed; Najam, Abdul Rahman (Al-Nahrain Journal for Engineering Sciences, 2020)
In this work it had been focused on the possibility of replacement of steel spring in suspension system by fiber reinforced polymer composite that is responsible for light weight of spring which leads to reduces the weight of vehicle and improve fuel efficiency. This type of spring used in motor cycles, light weight vehicle. The design will be simulated by ANSYS workbench. Then, E-Glass fiber has been used to fabricate helical compression spring of 40% fiber volume fraction of glass. with polyester resin. The deflection of glass reinforced composite spring is more than steel spring but within permissible limit. weight of composite spring is reduced by 57% than of steel.